Domestication and Foreignization in two Translations of Julian Barnes' The Sense of an Ending - Afaf Alwan; Baleid Taha Shamsan; Gibreel Sadeq Alaghbary (Taez University, 2024)
The present study aims at exploring the translation strategies used in translating culturally loaded expressions in two translations of Julian Barnes' The Sense of an Ending. In particular, the study seeks to ascertain the extent to which cultural content is retained by the translators or domesticated to cater the target language audience. To attain this objective, translation units are purposively selected and compared across the two translations. Analysis has revealed that Masaud's translation is ST-oriented and characterized by an overreliance on literal translation. The translator either avoids translating cultural content, specifically religious references and taboo expressions, or offers a translation that respects the ST more than the TL audience, resulting in a translation that sends the reader abroad (Venuti 1995). In comparison, Faisal's translation is TT-oriented and brings the author back home. It domesticates the foreign text to target-language cultural values. The study concludes that Faisal's translation is more fluent and natural because it minimizes the foreignness of the source-text, while Masaud's translation, which champions accuracy at the expense of acceptability, doubles the cognitive demands on the reader by offering translations that fail to fit in comfortably with the established cultural reference framework.